The Inaccessible Environment in Public Transport for Blind People - Todorova, Rumyna (Research Papers, 2025)
This paper will focus on accessibility and mobility of society, and in particular people with disabilities. The purpose of the study is to expose the factors favoring the free movement of man and the challenges he faces. Access to public services such as public transport is a social right that should not be neglected in the 21st century.